1991
DOI: 10.1016/0270-9139(91)92469-o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interferon administration on serum hepatitis C virus RNA in patients with chronic hepatitis C

Abstract: Hepatitis C virus RNA as detected by reverse transcription and nested polymerase chain reaction was monitored in 16 patients with chronic hepatitis C treated with interferon. Hepatitis C virus RNA became undetectable after 4 to 8 wk of interferon administration in 13 of the 16 patients. During 6 mo of follow-up, 5 of the 13 patients who became negative for hepatitis C virus RNA after interferon administration remained negative, and all five continued to have normal ALT levels. Repeat liver biopsy in these five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 0 publications
3
61
0
Order By: Relevance
“…Currently, interferon (IFN) is the only drug that induces viral clearance and marked biochemical and histological improvement (1)(2)(3)(4)(5)(6). During IFN administration, the serum level of hepatitis C virus (HCV)-RNAwas negative by reverse transcription nested polymerase chain reaction (RT-PCR), in about 50-80%patients.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, interferon (IFN) is the only drug that induces viral clearance and marked biochemical and histological improvement (1)(2)(3)(4)(5)(6). During IFN administration, the serum level of hepatitis C virus (HCV)-RNAwas negative by reverse transcription nested polymerase chain reaction (RT-PCR), in about 50-80%patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to our estimation of the carcinogenesis rates in untreated patients with chronic hepatitis C, 7 5-year, 10-year, and 15-year rates were 4.8%, 13.6%, and 26.0%, respectively. Because life expectancy of patients with HCV-related cirrhosis is largely influenced by development of HCC in the clinical course, and because an effective and truly curative therapy for HCC still remains limited at best, primary prevention of HCC in patients with chronic liver disease is of great importance.Interferon (IFN) is effective in eliminating HCV and in reducing serum alanine transaminase (ALT) in some patients with chronic hepatitis C. [8][9][10][11] The response to IFN therapy is related to factors including HCV subtype, serum concentration of HCV, IFN treatment schedule, and liver histology. 11-14 A Japanese trial of IFN for patients with HCV-related cirrhosis showed that IFN therapy decreased the HCC appearance rate through the disappearance of HCV RNA.…”
mentioning
confidence: 99%
“…Interferon (IFN) is effective in eliminating HCV and in reducing serum alanine transaminase (ALT) in some patients with chronic hepatitis C. [8][9][10][11] The response to IFN therapy is related to factors including HCV subtype, serum concentration of HCV, IFN treatment schedule, and liver histology. [11][12][13][14] A Japanese trial of IFN for patients with HCV-related cirrhosis showed that IFN therapy decreased the HCC appearance rate through the disappearance of HCV RNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The only drug that effectively reduces the virus load is interferon (IFN), but complete eradication of the virus occurs in only some treated patients. [5][6][7][8] Currently, genotype 1b and a high virus titer are well-established predictive factors of a poor response to IFN. [9][10][11] Enomoto et al, 12,13 recently reported that amino-acid-sequence substitutions in a 40 amino acid stretch (codons 2209-2248) in the NS5A region of HCV genotype 1b are tightly associated with the outcome of IFN therapy, and designated this region as the IFN-sensitivity-determining-region (ISDR).…”
mentioning
confidence: 99%